2009
DOI: 10.1186/1471-2164-10-627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on gene expression in embryos of the coral Montastraea faveolata

Abstract: BackgroundCoral reefs are expected to be severely impacted by rising seawater temperatures associated with climate change. This study used cDNA microarrays to investigate transcriptional effects of thermal stress in embryos of the coral Montastraea faveolata. Embryos were exposed to 27.5°C, 29.0°C, and 31.5°C directly after fertilization. Differences in gene expression were measured after 12 and 48 hours.ResultsAnalysis of differentially expressed genes indicated that increased temperatures may lead to oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
140
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(169 citation statements)
references
References 45 publications
21
140
3
Order By: Relevance
“…In addition, it is worthwhile to investigate in the future the impairment of Ca 2+ release as a part of the overall suppression of exocytosis and apoptosis in corals (17,43,44), as Ca 2+ is known signal for apoptosis initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is worthwhile to investigate in the future the impairment of Ca 2+ release as a part of the overall suppression of exocytosis and apoptosis in corals (17,43,44), as Ca 2+ is known signal for apoptosis initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although bleaching is highly correlated with increased temperature and high solar irradiance (6-10), it does not always lead to death of the cnidarian host (11)(12)(13). However, the physiological and molecular mechanisms that lead to death of the cnidarian are not adequately understood (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Especially considering reports that some larvae may digest the symbionts instead of engaging in a symbiotic relationship (Titlyanov et al, 1998;Mies et al, 2017c). The available gene expression studies are inconclusive in regard to whether the observed gene expression changes in coral larvae are specific to the symbiont exposure (deBoer et al, 2007;Voolstra et al, 2009a;Schnitzler and Weis, 2010;Mohamed et al, 2016). For instance, it is unclear if these changes are related to a mutualistic relationship or to the mere presence of a foreign algal body.…”
Section: Is There a Mutualism From The Start?mentioning
confidence: 99%
“…More recently, several studies have used gene expression approa ches to detect responses at a molecular level of both coral embryos and larvae subjected to elevated temperatures (e.g. Rodriguez-Lanetty et al 2009, Voolstra et. al 2009, Polato et al 2010, Portune et al 2010.…”
Section: Introductionmentioning
confidence: 99%